18 SEDATIVE LOAD IN COMMUNITY-DWELLING OLDER ADULTS WITH MILD–MODERATE ALZHEIMER'S DISEASE: LONGITUDINAL RELATIONSHIPS WITH ADVERSE EVENTS, DELIRIUM AND FALLS. (18th November 2021) - Dyer, A; Murphy, C; Lawlor, B; Kennelly, S
Abstract: Background: Older adults are frequently prescribed medications with sedative effects, which are associated with numerous adverse consequences. However, the use and longitudinal associations of sedative medication use in older adults with mild–moderate Alzheimer Disease (AD), has not been explored to date. Methods: The association between Sedative Load (SL) and adverse events, unscheduled healthcare utilisation, delirium and falls over 18 months was assessed in older adults with mild–moderate AD from 9 Countries. Additionally, the impact of SL on dementia progression was evaluated. Results: Over half (52.35%; 267/510) of those with mild–moderate ad (72.8 ± 8.26 years, 61.89%) were prescribed a regular medication with sedation as a primary effect or prominent side effect with 17.65% (90/510) having a high SL (≥3). The most common medications contributing to SL were antidepressants, antipsychotics, anxiolytics and hypnotics. Over 18 months, greater SL was associated with adverse events (IRR 1.18, 1.14–1.23, p < 0.001)/serious adverse events (IRR 1.32, 1.18–1.49, p < 0.001) and unscheduled GP visits (IRR 1.26, 1.15–1.38, p < 0.001). Further, increasing SL was associated with greater likelihood of incident delirium (IRR 1.47, 1.25–1.73, p < 0.001) and falls (IRR 1.25, 1.06–1.48, p = 0.007) which persisted after covariate adjustment. SL was not associated with accelerated cognitive decline or ad progression. Conclusion: Most adults with mild–moderate ad are prescribed at least one drug with a sedative effect and a significant minority have a high SL. Increasing SL was associated with a greater likelihood of experiencing adverse events, delirium and falls, highlighting the need for optimal prescribing in this vulnerable cohort.